2002
DOI: 10.1021/jf025841z
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric Procyanidins as Radical-Scavenging Components in Red-Hulled Rice

Abstract: The extracts from white-, black-, and red-hulled rice were prepared by sequential extraction with six different polar solvents, and their radical-scavenging activities were measured by methods using 1,1-diphenyl-2-picrylhydrazyl radical (DPPH*) and tert-butyl hydroperoxyl radical (t-BuOO*). The extracts prepared with highly polar solvents, methanol and deionized water, exhibited higher DPPH* and t-BuOO* scavenging activities in all three cultivars. In addition, the acetone extract from red-hulled rice exhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
140
2
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(156 citation statements)
references
References 19 publications
11
140
2
3
Order By: Relevance
“…In red pericarp grains, a high correlation was observed between this activity and the content of proanthocyanidins, but in the case of black pericarp grains the correlation depended on the content of anthocyanins (Oki et al, 2002). These results suggested that the phenolic compounds were among the main responsible ones for the antioxidant activity of rice grains (Goffman and Bergman, 2004).…”
Section: Antioxidant Activity and Biological Effectmentioning
confidence: 94%
See 1 more Smart Citation
“…In red pericarp grains, a high correlation was observed between this activity and the content of proanthocyanidins, but in the case of black pericarp grains the correlation depended on the content of anthocyanins (Oki et al, 2002). These results suggested that the phenolic compounds were among the main responsible ones for the antioxidant activity of rice grains (Goffman and Bergman, 2004).…”
Section: Antioxidant Activity and Biological Effectmentioning
confidence: 94%
“…In rice grains with red and black pericarp, the main phenolics are the anthocyanins cyanidin-3-O-β-Dglucoside and peonidin-3-O-β-D-glucoside (Oki et al, 2002;Hu et al, 2003;Chen et al, 2006;Zhang et al, 2006;Yawadio et al, 2007). Other compounds identified include the anthocyanidins cyanidin and malvidin (Hyun and Chung, 2004;Zhang et al, 2006), the anthocyanins pelargonidin-3,5-diglucoside and cyanidin-3,5-diglucoside (Zhang et al, 2006) and phenolic acids, like ferulic, caffeic and protocatechuic acids (Morimitsu et al, 2002).…”
Section: Phenolic Compounds In Ricementioning
confidence: 99%
“…The red pigment in rice grains is proanthocyanidin, also called condensed tannins (Oki et al, 2002). Proanthocyanidins are a branch off the anthocyanin pathway and share many of the same biosynthetic genes (Winkel-Shirley, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Oki et al indicated that the proanthocyanidin in the extracts of red-hull rice was the procyanidin type, which possess a DP ranging from 1 to 38 monomer. 11) Whereas, the proanthocyanidin in grape seed is procyanidin type and represents major oligomer with DP4 (60%). 17) Based on Sephadex LH gel filtration column chromatography, the PRFR was co-eluted at the same fractions (fraction numbers 27 to 29) as the proanthocyanidin from grape seed extract as shown in the supplement data 1.…”
Section: Discussionmentioning
confidence: 99%
“…Type Identification of Proanthocyanidin in PRFR To elucidate the constituent of proanthocyanidin in PRFR, HPLC of the acid hydrolyses of PRFR was performed according to the method described by Oki et al 11) Briefly, 10 mg of PRFR was dissolved in 1 mL of 1.0 M HCl and the mixture was hydrolyzed in boiling water for 30 min. The hydrolysate was re-dissolved in 1.0% (v/v) trifluoroaetic acid (TFA) solution.…”
Section: Methodsmentioning
confidence: 99%